2015
DOI: 10.2106/jbjs.n.01275
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Osteoporotic Therapy After Fragility Fracture Lowers Rate of Subsequent Fracture

Abstract: Treatment with anti-osteoporotic therapy after a fragility fracture leads to a 40% decrease in the three-year risk of subsequent fracture, when adjusted for age and sex. Initiation of anti-osteoporotic therapy following a fragility fracture can prevent a subsequent fracture over the following three years in approximately one of every twenty-seven patients treated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
52
0
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 37 publications
1
52
0
9
Order By: Relevance
“…[27][28][29] Bawa et al assessed osteoporosis care after fragility fracture in over 31 000 patients and found that only 10.6% of patients were treated with anti-osteoporotic medications following the index fracture. 30 In the 10.6% of patients that did receive anti-osteoporotic therapy, there was a 40.6% reduction in subsequent fractures. 30 Hawley et al assessed the results following governmental recommendations that hip fracture patients were prescribed bisphosphonates for secondary fracture prevention in Great Britain and found that 3 years after the initiation of the intervention, there was a 22% reduction in subsequent hip fracture and a 14% reduction in major osteoporotic fracture (including vertebral fractures).…”
Section: Vertebral Fragility Fracturementioning
confidence: 97%
See 3 more Smart Citations
“…[27][28][29] Bawa et al assessed osteoporosis care after fragility fracture in over 31 000 patients and found that only 10.6% of patients were treated with anti-osteoporotic medications following the index fracture. 30 In the 10.6% of patients that did receive anti-osteoporotic therapy, there was a 40.6% reduction in subsequent fractures. 30 Hawley et al assessed the results following governmental recommendations that hip fracture patients were prescribed bisphosphonates for secondary fracture prevention in Great Britain and found that 3 years after the initiation of the intervention, there was a 22% reduction in subsequent hip fracture and a 14% reduction in major osteoporotic fracture (including vertebral fractures).…”
Section: Vertebral Fragility Fracturementioning
confidence: 97%
“…30 In the 10.6% of patients that did receive anti-osteoporotic therapy, there was a 40.6% reduction in subsequent fractures. 30 Hawley et al assessed the results following governmental recommendations that hip fracture patients were prescribed bisphosphonates for secondary fracture prevention in Great Britain and found that 3 years after the initiation of the intervention, there was a 22% reduction in subsequent hip fracture and a 14% reduction in major osteoporotic fracture (including vertebral fractures). 31 The recommendations for assessing and managing osteoporosis are not vague or difficult to find; compliant implementation of these measures results in >40% to 80% reduction in subsequent fragility fracture of the spine.…”
Section: Vertebral Fragility Fracturementioning
confidence: 97%
See 2 more Smart Citations
“…Equally important is the need for anti-osteoporotic medication treatment. "Anti-Osteoporotic Therapy After Fragility Fracture Lowers Rate of Subsequent Fracture: Analysis of a Large Population Sample," the study by Bawa et al in this issue of The Journal, demonstrates the benefit of adequate anti-osteoporotic therapy in reducing recurrent fragility fractures 11 . Although we as orthopaedic surgeons may not be comfortable prescribing these medications, by investing in a fragility fracture program such as Own the Bone, a system can be designed to ensure that anti-osteoporotic medication treatment is addressed with our patients.…”
mentioning
confidence: 99%